Study of SRB adherence on carbon steel by electrochemical and microscopic techniques - Viera, Marisa (2017)
It is well known that microbiologically influenced corrosion (MIC) is a serious issue in the oil and gas industry. This process is caused by a mixture of microorganisms, including aerobic and anaerobic bacteria. Among the later, the Sulfate Reducing Bacteria (SRB) are often designated as the pricipal organisms responsible for MIC in anaerobic environments such as those found in the oil extraction industry. Extracellular polymeric substances (EPS) produced by SRB have the ability to accelerate corrosion by binding with metal ions. The aim of this study was to evaluate the formation of biofilms of SRB on carbon steel surfaces by electrochemical and microscopic techniques.